4 film favorites. Free Willy collection [videorecording (DVD)]. - Richter, Jason James; Petty, Lori; Atkinson, Jayne; Schellenberg, August; Madsen, Michael; Walker, Keith A., 1935-1996; Blechman, Corey; Tugend, Jennie Lew; Shuler-Donner, Lauren; Wincer, Simon; Tenney, Jon, 1961-; Peña, Elizabeth, 1959-2014; et al. (Warner Home Video, 2010)
Free Willy (1993, 112 min.): A boy risks everything to save a beloved killer whale when he learns the aquarium owners are going to kill it.